Criminal Law: Combating Crimes in Financial Sphere - KAZIMOV, Mirali S. (Journal of Advanced Research in Law and Economics, 2017)
The article identifies that crime in the financial sphere as a socially dangerous act that infringes on economic and financial relations regulated by the norms of financial (tax) law, the formation, distribution, redistribution and use of funds of funds (financial resources) of States, local governments, and other business entities. It is shown that the social danger of crimes in credit-financial sphere is that as a result of such infringement is caused or created a real possibility of significant harm to the economic interests of the state, as well as other subjects related to financial activities. The authors propose to consider the criminal law not only as an institution of punishment, but also as an institution of transmission of the shadow part of the economy in the public area. This article provides analysis of the legal norms and special complex types are defined the way of development and structuring situations of counteraction to criminal law.